2020
DOI: 10.3390/ma13215004
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cement-Based Superhydrophobic Composite Coating: New Option for Water Drainage Pipeline Rehabilitation

Abstract: A great number of urban underground concrete water drainage systems in China are facing challenges of corrosion, blockage, and leakage. This could result in engineering accidents such as urban inland inundation, pipeline collapse, leakage, and blockage. The common contributing factors for pipeline leakage and blockage are the porous structures and the perishable surfaces of concrete pipes. To address these issues, we synthesized superhydrophobic coating materials such as SiO2 aerosol, bisphenol A diglycidyl et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The specific reason is that the modified material can significantly enhance the dispersion ability between fiber and cement, better combine the matrix and fiber material, increase the interfacial adhesion, and thus, enhance the overall flexural strength of the material. The modified PVA fiber matrix is an ideal material for underground infrastructure reconstruction [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specific reason is that the modified material can significantly enhance the dispersion ability between fiber and cement, better combine the matrix and fiber material, increase the interfacial adhesion, and thus, enhance the overall flexural strength of the material. The modified PVA fiber matrix is an ideal material for underground infrastructure reconstruction [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have been conducted to facilitate a better understanding and control of the deterioration process of sewer concrete pipeline structures, through a variety of research works [ 14 , 15 , 16 ]. Some chemical acids were used as the corrosive agents of the concrete material corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Feng [21] found that mortar became hydrophobic by addition of stearic acid aqueous emulsion, the resistance of water and chloride penetration into concrete was enhanced, but the mechanical strength declined severely. Polymers were also used to modify the surface of cement-based materials [22][23][24][25][26], and the durability was improved [27][28][29][30][31]. Some hydrophobic metal soaps were also used to modify the properties of concrete by depositing hydrophobic layers on the pore surface, but there were doubts about their long-term effects.…”
Section: Introductionmentioning
confidence: 99%